Multidirectional instability of the shoulder: surgical techniques and clinical outcome. - Şahin, Koray; Kendirci, Alper Şükrü; Albayrak, Muhammed Oğuzhan; Sayer, Gökhan; Erşen, Ali (My University, 2022)
Multidirectional instability of the shoulder has a complex pathoanatomy. It is characterized by a redundant glenohumeral capsule and increased joint volume. Subtle clinical presentation, unclear trauma history and multifactorial etiology poseses a great challenge for orthopedic surgeons in terms of diagnosis. Generally accepted therapeutic approach is conservative and the majority of patients achieve good results with rehabilitation. In patients who are symptomatic despite appropriate rehabilitation, surgical intervention may be considered. Good results have been obtained with open inferior capsular surgery, which has historically been performed in these patients. In recent years, advanced arthroscopic techniques have taken place in this field, and similar results compared to open surgery have been obtained with the less-invasive arthroscopic capsular plication procedure.
Keywords: arthroscopic capsular plication; multidirectional shoulder instability; open inferior capsular shift